Faith-Based Initiatives in Response to HIV/AIDS in Jamaica - Muturi, Nancy W. (My University, 2010)
HIV/AIDS continues to advance relentlessly in the developing countries with the Caribbean ranking second to sub-Saharan Africa in rates of infection. Using the social influence theory that recognizes the role of opinion leaders in social and behavioral change, this study examines the contributions of faith-based organizations (FBOs) in addressing the HIV/AIDS epidemic in Jamaica. Through data gathered qualitatively from FBO members and persons living with HIV/AIDS (PLWHA), this article demonstrates that religion plays a crucial role in the Jamaican culture and that religious leaders have the potential to address the widespread HIV/AIDS epidemic in their communities. Many of them have established programs that provide social, psychological, and physical support and have collaborated with health organizations to initiate health educational programs that seek to impact understanding to motivate behavioral change. This FBO integrative approach complements mass media public awareness HIV/AIDS campaigns but is hampered by HIV/AIDS-related stigma, socio-cultural and religious beliefs, the lack of HIV/AIDS policies, and the inadequate capacity among religious leaders to address the epidemic. This article recommends further research on strategies to incorporate spirituality into health communication interventions, as well as on the overall impact of the FBO approach to HIV/AIDS prevention in the Caribbean region.
Keywords: HIV/AIDS; Social influence theory; Faith-based organizations; Spirituality; Health communication